Learning from gain and loss: Links to suicide risk. (March 2022) - Dixon-Gordon, Katherine L.; Waite, Elinor E.; Ammerman, Brooke A.; Haliczer, Lauren A.; Boudreaux, Edwin D.; Rathlev, Niels; Cohen, Andrew L.
Abstract: Despite preliminary evidence that people with suicide attempt histories demonstrate deficits in processing feedback, no studies have examined the interrelations of learning from feedback and emotional state on suicide risk. This study examined the influence of suicide risk and negative emotions on learning accuracy and rates among individuals with a range of borderline personality features ( N  = 145). Participants completed a reinforcement learning task after neutral and negative emotion inductions. Results revealed interactions between suicide risk and emotion condition, with elevated risk linked to greater increases in loss learning rate (training phase models) and gain learning rate (test phase models) post-negative emotion induction. Emotion-dependent fluctuations in learning performance may be markers of decision-making that are associated with greater suicide risk. This line of work has the potential to identify the contexts that confer greater risk for suicidal behaviors. Highlights: Suicide risk was not associated with overall learning accuracy. Suicide risk was linked to increased loss learning rate post-stressor. Suicide risk was linked to increased gain learning rate post-stressor. Emotions may influence decision-making in the context of suicide risk.